Income from non-timber forest products - Arnold, J.E.M.; Ruíz Pérez, M. (2000)
NTFPs can be of particular importance to people in forested mountain locations, because of their relative lack of access to alternative inputs and sources of income. Mountain forest uses centred on NTFPs can show a clearer link between conservation and development potentials due to the reduced opportunities to intensify use of natural resources and to a greater local awareness of environmental constraints. This places great importance on effective government policies, legislation and practices that establish and protect the use and management rights of those who rely on the related forest and tree resources, and equally underlines the need for interventions that support rather than impede the ability of mountain NTFP producers to appropriately respond to new or expanded market opportunities as they emerge.